Influence o f intradot Coulomb interaction on transport properties of an Aharonov-Bohm interferometer - Son, Do Ngoc; Cong, Bach Thanh (VNU Journal of Science: Mathematics - Physics; Vol 23 No 1, 2007)
Using Greens íunction method and the equation o f motion approach, we have investigated the electronic transport properties o f an Aharonov-Bohm (AB) ring in the presence o f a magnetic field with a quantum dot inserted in one arm o f the ring. In particular, we consider the electron-electron Coulomb interaction within the quantum dot. We find that the current through the system is dependent on the magnetic flux via the AB phase and the Coulomb interaction within the quantum dot, in agreement with experiments. Furthermore, the intradot Coulomb interaction induces dephasing.